Emotional (UN) Wellness in Learning Speaking Among University Students - Lalu Jaswadi Putera; Lalu Nurtaat; Juliandri Maya Chrysty (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
Emotional (un)wellness in the time of learning speaking among university students is recognized as an important issue, thus more data on students’ psychological problems level and effective strategies to overcome such problems are needed. All enrolled 2nd semester students from English Education Department at the University of Mataram were invited to complete an online-based survey. The psychological problems were assessed using qualitative method. Results showed that the psychological problems encountered by the students included: anxiety (62%, High), fear of making mistakes (54%, Moderate), feeling embarrased (48%, Moderate), lack of confidence (51%, Moderate), and lack of motivation (19%). Leading psychological problem is anxiety that comprises more than one tenth percent of the total problems. The main causes of the problems were associated with: fear of negative responses from the classmates, fear of sounding silly when speaking, and feeling embarassed to speak. In coping with these problems, the students preferred to use talk-to-the-mirror and talk-to-a-friend methods. Despite the many problems, majority of the students have very low demotivation level (19%), meaning that they have very high motivation to learn, to participate and to improve their speaking competence in learning speaking (81%). These results provide evidence that psychological problems in learning speaking among university students do exist. They also highlight the need for serious efforts to overcome the problems.